1995
DOI: 10.1111/j.1365-2133.1995.tb02616.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of stem cell factor in cutaneous mastocytosis

Abstract: Stem cell factor has recently been identified as a potent growth factor for bone marrow stem cells, melanocytes and mast cells. In order to evaluate its possible role in human mastocytosis, skin lesions from 13 patients with urticaria pigmentosa and five patients with mastocytomas, and normal skin specimens from five healthy donors were studied by immunohistochemistry, using polyclonal and monoclonal (hkl-12) antibodies against stem cell factor, and a monoclonal antibody (YB5.B8) against its receptor, the c-ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
34
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 25 publications
7
34
0
1
Order By: Relevance
“…Most SCF in human epidermis has been reported to be expressed as the membrane-bound type, which is not released into intercellular spaces between keratinocytes. 66,67 It has also been suggested that the membrane-bound form of SCF is expressed on the plasma membrane of keratinocytes and activates the c-kit receptor persistently without c-kit internalization and degradation within melanocytes. 68 Consistent with this, our previous study on UVB-induced human pigmentation demonstrated that the membrane-bound form, but not the soluble form, of SCF was significantly increased in the UVB-exposed epidermis.…”
Section: Discussionmentioning
confidence: 99%
“…Most SCF in human epidermis has been reported to be expressed as the membrane-bound type, which is not released into intercellular spaces between keratinocytes. 66,67 It has also been suggested that the membrane-bound form of SCF is expressed on the plasma membrane of keratinocytes and activates the c-kit receptor persistently without c-kit internalization and degradation within melanocytes. 68 Consistent with this, our previous study on UVB-induced human pigmentation demonstrated that the membrane-bound form, but not the soluble form, of SCF was significantly increased in the UVB-exposed epidermis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that SCF is one of the most important factors influencing the number, phenotype and function of connective tissue type mast cells in health and disease [8, 9, 10]; however, its production and expression in connective tissue diseases have yet to be examined. In this study, we have examined the expression of SCF in the lesional skin of scleroderma by immunohistochemistry to investigate the possible role of SCF in the fibrotic process of scleroderma.…”
Section: Introductionmentioning
confidence: 99%
“…Kit is expressed on both mature MCs and their earliest progenitors (10) as well as on cells of erythroid and melanocytic lineages and on germ cells (11). Kit ligand (KL; also known as stem cell factor), is expressed in membrane-associated and soluble forms (12) by mast cells (13), fibroblasts (11), endothelial cells (14), stromal cells (15), keratinocytes (16), neuroblastoma cells (17), and tumor cell lines (18). Although KL represents a major growth and differentiation factor for both murine and human MCs (19,20), it also promotes Kit-dependent MC mediator release (21)(22)(23), as well as enhances the release of MC mediators via IgE-dependent mechanisms (22,24).…”
mentioning
confidence: 99%